Cardiac Tamponade as an Initial Manifestation of Cervical Cancer - Yuridia Evangelina Rodríguez-Rosales; Carlos Eduardo Salazar-Mejía; Blanca Angélica Soto-Martínez; David Hernández-Barajas; Oscar Vidal-Gutiérrez; Gabriela Sofia Gómez-Macías (Case Reports in Oncological Medicine)
Cervical cancer is the second most common malignancy worldwide in women and the third most common cause of cancer death in developing countries. This type of cancer spreads mainly to the lung, the bone, and the brain; however, the pericardium is an unusual site of invasion, which is associated with a poor prognosis. We present a case of a 35-year-old woman with six months of leg edema and abnormal uterine bleeding. During the initial evaluation, cardiac tamponade and a bilateral pleural effusion were found. A left supraclavicular lymphadenopathy was identified on physical examination, while gynecological examination and MRI were irrelevant. Initial cytology of the pericardial fluid showed a poorly differentiated carcinoma, and a cervical biopsy revealed a squamous cell invasive carcinoma. Chemotherapy was started with carboplatin and paclitaxel, but no clinical improvement was noted and the patient died 46 days after arrival. Cardiac tamponade in a young female patient is a harbinger to widen the differential diagnosis to include not only infectious, cardiac, or metabolic etiology but also oncological causes since this will allow appropriate treatment.